Spatial Navigation Is Impaired in Elderly Patients With Cerebral Small Vessel Disease - Zhào, Hóngyi; Chi, Liyi; Zhang, Yanhai; Huang, Yonghua; Tian, Hongyan (Frontiers in Neurology, 2021)
Cerebral small vessel disease (SVD) refers to a heterogeneous group of pathological processes that result from damage to the small penetrating vessels in the brain. Spatial navigation, one of the most fundamental behaviors, is becoming a clinical brand-new focus. This study aimed to determine whether spatial navigation performance is impaired in elderly SVD patients. In total, 18 elderly patients with severe SVD, 40 elderly patients with non-severe SVD, and 41 age-matched healthy volunteers were classified according to the Fazekas’ scale.. Spatial navigation was evaluated by Amunet (a computer-based analogy of Morris water maze software), as well as mini-mental scale evaluation (MMSE), category verbal fluency test (VFT), clock drawing test (CDT) and trail making test (TMT) -B were applied. Compared to healthy controls, SVD patients exhibited significantly worse performance on “allocentric + egocentric” and allocentric subtests, but not on egocentric subtest. The linear regression analysis revealed that allocentric navigation deficit was significantly correlated with TMT-B and CDT performance in elderly SVD patients. These results elucidated that spatial navigation ability could be a manifestation of cognitive deficits in elderly patients with SVD.